STATE FAILURE AS A FACTOR IN INTERNATIONAL GLOBAL COUNTERACTING OPERATIONS: NETWORK MODELING - A. Tikhomirov; A. Trufanov; A. Caruso; A. Rossodivita; R. Umerov; Z. Umerova (Kherson State University, 2012)
In the paper are considered the need for build cooperation and collaboration among all entities and actors. Comprehensive Network Lace is based on an end-to-end description of major categories of interactions for sets of entities using a multilayer (multi-level) variety of complex networks.